Exceptionally strong magnetism in the 4d perovskites RTcO3 (R = Ca, Sr, Ba) - SANVITO, STEFANO; ARCHER, THOMAS DAVID (My University, 2011)
The evolution of the magnetic ordering temperature of the 4d3 perovskites RTcO3 (R=Ca, Sr, Ba) and its relation with its electronic and structural properties has been studied by means of hybrid density functional theory and Monte Carlo simulations. When compared to the most widely studied 3d perovskites the large spatial extent of the 4d shells and their relatively strong hybridization with oxygen weaken the tendency to form Jahn-Teller like orbital ordering. This strengthens the superexchange interaction. The resulting insulating G-type antiferromagnetic ground state is characterized by large superexchange coupling constants (26?35 meV) and Neel temperatures (750?1200 K). These monotonically increase as a function of the R ionic radius due to the progressive enhancement of the volume and the associated decrease of the cooperative rotation of the TcO6 octahedra.
PUBLISHED
Keywords: Particles and fields physics; 4d perovskites